Evaluation of Adsorption Capacity of Low Cost Adsorbent for the Removal of Congo Red Dye from Aqueous Solution - Dattatraya B. Jirekar; Milind Ubale; Mazahar Farooqui (Orbital: The Electronic Journal of Chemistry, 2016)
Vigna unguiculata seed husk powder has been investigated as low cost adsorbent for the removal of hazardous chemicals like Congo Red (CR) dye from aqueous solution. Various parameters such as effect of contact time, initial CR dye concentration, adsorbent dose, effect of pH, zero-point pH were studied. Batch adsorption technique was employed to optimize the process parameter. The result indicated that, the percentage adsorption of Congo Red increased with increase in contact time, dose of adsorbent and initial concentration of Congo Red and decreased with addition of salt. The adsorption of Congo Red was 78% at the optimum pH of 6. Adsorption equilibrium was found to be reached in 24 h for 5 to 25 g/50 mL Congo red concentrations. The Langmuir and Freundlich isotherm models were found to provide an excellent fitting of the adsorption data.  The adsorption of CR follows Second order rate kinetics. Thermodynamic parameter (δGo) showed that it was an exothermic process. This adsorbent was found to be effective and economically attractive.DOI: http://dx.doi.org/10.17807/orbital.v8i5.834